Child and Adolescent Psychiatry and Mental Health - Fegert, Joerg M.; Brown, Rebecca; Eberle, Simone
Child and Adolescent Psychiatry and Mental Health, the official journal of the International Association for Child and Adolescent Psychiatry and Allied Professions, is an open access, online journal that provides an international platform for rapid and comprehensive scientific communication on child and adolescent mental health across different cultural backgrounds. CAPMH serves as a scientifically rigorous and broadly open forum for both interdisciplinary and cross-cultural exchange of research information, involving psychiatrists, paediatricians, psychologists, neuroscientists, and allied disciplines. The journal focusses on improving the knowledge base for the diagnosis, prognosis and treatment of mental health conditions in children and adolescents, and aims to integrate basic science, clinical research and the practical implementation of research findings. In addition, aspects which are still underrepresented in the traditional journals such as neurobiology and neuropsychology of psychiatric disorders in childhood and adolescence are considered.